Congenital Urethrocutaneous Fistula - Bijay Kumar Suman; Ram Jeewan Singh; Amit Kumar Sinha; Bindey Kumar (Wolters Kluwer Medknow Publications, 2024)
Male congenital urethrocutaneous fistula is an extremely rare anomaly that is commonly associated with chordee or anorectal malformations. It is characterised by an abnormal urethral opening on the ventral aspect of the penis with well-formed distal urethra and meatus at the tip of the glans. The treatment is individualised according to the site of the fistula, associated anomalies and condition of the distal urethra. The principles of hypospadias surgery should be strictly followed.